PESANTREN DIGITAL BRANDING THROUGH THE MANAGEMENT OF ISLAMIC EDUCATIONAL CONTENT ON YOUTUBE AND INSTAGRAM PLATFORMS - Jihan Muniroh; Abdul Aziz (Jurnal Manajemen Pendidikan, 2026)
The rapid development of social media has encouraged Islamic educational institutions, including pesantren (Islamic boarding schools), to utilize digital platforms for communication, da'wah (Islamic outreach), information dissemination, and institutional branding. However, studies on pesantren digital branding through the management of Islamic educational content remain limited, particularly those examining content management as an integral part of institutional branding strategies. This study aims to describe the management of Islamic educational content on the social media platforms of Pondok Pesantren Ma'unah in Purworejo Regency, identify the factors supporting and constraining its implementation, and analyze its contribution to pesantren digital branding. This study employed a qualitative approach with a case study design. Data were collected through observations, semi-structured interviews, and documentation involving eight informants, including the pengasuh (head of the Islamic boarding school), a social media administrator, santri (students), alumni, and members of the congregation. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña. The findings indicate that YouTube and Instagram are utilized to publish Islamic educational content, da'wah, and documentation of pesantren activities. Although content management remains relatively simple, continuous educational and religious activities sustain regular content publication. Social media also enhances institutional visibility, information transparency, alumni engagement, and the positive public image of the pesantren.